Pedagogical content knowledge of English teacher on reading comprehension during pandemic covid-19 with online classes in senior high school - R. Muchammad Aditya Rafianto Kusuma (Journal of Research on English and Language Learning (J-REaLL), 2022)
The research of Pedagogical Content Knowledge (PCK) uses a qualitative approach. The purpose of this research is to obtain the Pedagogical Content Knowledge (PCK) of prospective teachers of English Courses in terms of academic ability during the Covid-19 pandemic, as it is known that the pandemic has changed the structure of life that has been neatly arranged in this world. Data were analysed in the form of documents, observed, and interviewed with prospective English teachers on SMAN 15 SURABAYA. The technique of taking the data in this study was purposive sampling. The subjects in this study are teachers with more learning hours because in general they are categorized as professional teachers, then teachers with many teaching hours will be examined how the PCK is. The instruments in this study used CoRe and Vignette. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and conclusions. Based on the results of the study, it shows that the pedagogical content knowledge of English teachers on reading comprehension during the pandemic still needs more creative and innovative adjustments, this is indicated by the number of teachers who are still hampered during learning hours.